Virulence genes and antibiotic resistance profile of shiga toxin producing Escherichia coli and enterotoxigenic Escherichia coli from diarrhoeic cattles and human handlers in Asom (India) - LALHRUAIPUII; RAHMAN, H; SAIKIA, G K; KATARIA, J L; LALLAWMZUALI (The Indian Journal of Animal Sciences, 2017)
The present study was undertaken to isolate and characterize STEC and ETEC from diarrhoeic calves and humans in Asom, India. Out of the 134 presumptive Escherichia coli isolates picked from 80 diarrhoeic calves, 31 isolates could be serotyped into 23 different serogroups; and out of 19 strains of E. coli from human beings, 13 strains could be serotyped into 10 different serogroups. O157 from cattle and O131 from humans were the frequently encountered serogroups. The virulence gene profile of the STEC and ETEC isolates showed that the prevalence of stx2 gene and the emergence of multi drug resistant STEC and ETEC isolates in high proportion indicates that they may act as an important reservoir posing a possible threat to public health and may complicate future therapeutic options.